Consultation-liaison psychiatry services in Pakistan: bridging gaps and revealing new opportunities - Aisha Noorullah; Hambal, Ifrah; Ishtiaq, Zoha; Zaman, Mohammad; Pirani, Shahina; Khan, Murad Moosa (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the demographic, clinical and service-related characteristics of psychiatric referrals received by a consultation-liaison service in a multidisciplinary setting. Method: The descriptive, observational, retrospective study was conducted from January to June 2022 at the Aga Khan University Hospital, Karachi, and comprised data from March 2020 to December 2021 of all inpatients and those reporting to the Accident and Emergency Department who were referred to institutional consultation-liaison psychiatry service. Data was analysed using SPSS 19). Results: Of the 2,838 referrals, 1,427(50.3%) were for female patients and 1,411(49.7%) were for male patients. The most referred age group was 21-40 years 1,049(37%), followed by 61-100 years 744(26.2%). Among the referred patients, 1,522(53.6%) were inpatients and 1,316(46.4%) were those who had reported to the Accident and Emergency Department. There were 2,273(80%) urgent referrals, with confused and agitated behaviour being the most common reason 618(21.8%). Delirium was the most frequent diagnosis 524(18.5%), followed by depressive disorder 341(12%). Outpatient clinic follow-up was completed by 1,902(67%) patients. Delirium was more prevalent in males compared to females (p<0.001), while females were more frequently diagnosed with depression than males (p<0.001). Inpatients were more often referred for confused and agitated behaviour (p=0.014), whereas those referred by the Accident and Emergency Department related to anxiety (p<0.001). Conclusion: The consultation-liaison psychiatry service received a large number of referrals, highlighting the growing demand for integrated mental health services in healthcare settings. Key Words: Consultation-liaison psychiatry, Referral and consultation, Mental health services.